Genotypic diversity among rhizospheric bacteria of three legumes assessed by cultivation-dependent and cultivation-independent techniques - Pongsilp,N. (Springer Netherlands, 2015)
The genotypic diversity of rhizospheric bacteria of 3 legumes including Vigna radiata, Arachis hypogaea and Acacia mangium was compared by using cultivation-dependent and cultivation-independent methods. For cultivation-dependent method, Random amplified polymorphic DNA (RAPD) profiles revealed that the bacterial genetic diversity of V. radiata and A. mangium rhizospheres was higher than that of A. hypogaea rhizosphere. For cultivation-independent method, Denaturing gradient gel electrophoresis (DGGE) profiles of PCR-amplified 16S rRNA genes revealed the difference in bacterial community and diversity of rhizospheres collected from 3 legumes. The ribotype richness which indicates species diversity, was highest in V. radiata rhizosphere, followed by A. hypogaea and A. mangium rhizospheres, respectively. Three kinds of media were used to cultivate different target groups of bacteria. The result indicates that the communities of cultivable bacteria in 3 rhizospheres recovered from nutrient agar (NA) medium were mostly different from each other, while Bradyrhizobium selective medium (BJSM) and nitrogen-free medium shaped the communities of cultivable bacteria. Nine isolates grown on BJSM were identified by 16S rRNA gene sequence analysis. These isolates were very closely related (with 96% to 99% identities) to either one of the three groups including Cupriavidus-Ralstonia group, Bacillus group and Bradyrhizobium-Bosea-Afipia group. The rhizospheres were also examined for their enzymatic patterns. Of 19 enzymes tested, 3 rhizospheres were distinguishable by the presence or the absence of leucine acrylamidase and acid phosphatase. The selected cultivable bacteria recovered from NA varied in their abilities to produce indole-acetic acid and ammnonia. The resistance to 10 antibiotics was indistinguishable among bacteria isolated from different rhizospheres. © 2011 Springer Science+Business Media B.V.